2005
DOI: 10.1210/jc.2004-1355
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Induces Apoptosis and Cell Cycle Arrest in Poorly Differentiated Thyroid Cancer Cells

Abstract: Poorly differentiated thyroid carcinoma is an aggressive human cancer that is resistant to conventional therapy. Histone deacetylase inhibitors are a promising class of drugs, acting as antiproliferative agents by promoting differentiation, as well as inducing apoptosis and cell cycle arrest. Valproic acid (VPA), a class I selective histone deacetylase inhibitor widely used as an anticonvulsant, promotes differentiation in poorly differentiated thyroid cancer cells by inducing Na(+)/I(-) symporter and increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
1
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 34 publications
5
69
1
2
Order By: Relevance
“…We have reported elsewhere that VPA, at a concentration of 1 mM, induces cell re-differentiation (Fortunati et al 2004) and apoptosis (Catalano et al 2005) in poorly differentiated thyroid cancer cells. The former effect depends on the ability of VPA to restore NIS expression and its membrane localization; the latter is related to the VPA-induced up-regulation of p21 and down-regulation of cyclin A, at both mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We have reported elsewhere that VPA, at a concentration of 1 mM, induces cell re-differentiation (Fortunati et al 2004) and apoptosis (Catalano et al 2005) in poorly differentiated thyroid cancer cells. The former effect depends on the ability of VPA to restore NIS expression and its membrane localization; the latter is related to the VPA-induced up-regulation of p21 and down-regulation of cyclin A, at both mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 95%
“…Conversely, valproic acid (VPA), a potent anti-convulsant widely used to treat epilepsy and mood disorders that acts as an HDAC inhibitor at therapeutic concentrations (Gottlicher et al 2001, Phiel et al 2001, produces mild adverse effects in man even when serum levels exceed the normal therapeutic range. We recently showed that, at concentrations reached in the serum of patients treated for epilepsy, VPA promotes iodine uptake (Fortunati et al 2004) and controls cell growth (Catalano et al 2005) in vitro in poorly differentiated thyroid cancer cells. In addition to its redifferentiating property, VPA has been reported to affect the growth of several transformed cells (Slesinger & Singer 1987, Knupfer et al 1988, Abdul & Hoosein 2001, Olsen et al 2004, and to induce apoptosis in human leukemia cell lines (Kawagoe et al 2002) and endometrial cancer cells (Takai et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…VPA has been shown to inhibit growth in several tumor cell lines (13,19,20,24). To date, the effect of VPA treatment on SCLC cell growth has not been characterized.…”
Section: Vpa Inhibits Proliferation Of Sclc Cellsmentioning
confidence: 99%
“…In addition, VPA acts as a specific inhibitor of class I HDACs and induces proteasomal degradation of HDAC2, leading to cellular differentiation, growth arrest, and death in vivo and in vitro (Göttlicher et al, 2001;Phiel et al, 2001;Krämer et al, 2003;Catalano et al, 2005).…”
mentioning
confidence: 99%